Balloon angioplasty of cardiac vein in a patient treated by cardiac resynchronization therapy - Đurić Predrag; Mladenović Zorica; Drobnjak Dragan; Spasić Marijan; Jović Zoran; Đurić Ivica; Bogdanović Predrag; Romanović Radoslav; Milašinović Goran (Vojnosanitetski Pregled)
Introduction. Cardiac resynchronization therapy (CRT) reduces mortality and hospitalization in patients with symptomatic heart failure and left bundle branch block (LBBB) on optimal drug therapy. Among all, the reasons for “non-response” to CRT pacemaker could be the failure to achieve optimal left ventricular (LV) lead position due to severe curve or stenosis/occlusion of the target vein. Case report. We presented a 79-old-male patient, New York Heart Association (NYHA) class III, with atrial fibrillation, chronic coronary syndrome (CCS), and prior myocardial infarction. The patient underwent coronary artery bypass surgery and mechanical prosthetic aortic valve implantation. He was indicated for CRT. The patient′s venogram revealed ostial/proximal severe curve and stenosis of the posterolateral vein, the only vein of coronary sinus that led to anatomically optimal LV segment for stimulation. After the balloon angioplasty of the curved and stenotic portion of the target vein with compliant balloon 4.0 × 30 mm, a satisfactory and stable position of quadripolar LV lead was achieved. Conclusion. Compliant balloon angioplasty could be a safe and efficient way to override severe coronary vein stenosis in some CRT cases.